Навчання персоналу як ефективний інструмент організаційного розвитку - Лінькова, Олена Юріївна (Національний університет харчових технологій, 2021)
У статті досліджено значення організаційного розвитку для забезпечення конкурентоспроможності. Запропоновано збалансовану модель організаційного розвитку на основі системи навчання, яка містить: дослідження ринкового попиту та споживчих цінностей; закріплення бізнес-моделі в стратегічному управлінні; аудит кадрового потенціалу; формування системи навчання за проектом навичок; запровадження структурного компоненту управління змінами на основі стратегічного лідерства. Ризиками використання збалансованої системи навчання в межах обраної бізнес-моделі є: підвищення амбіцій персоналу; складність оцінки результатів навчання; підготовка навчальних програм. Заходами щодо мінімізації ризиків запровадження збалансованої системи навчання є: командна робота; формування структурного підрозділу коучів; укладення довгострокових угод на визначені програми навчання; системи мотивації.

The article examines the importance of organizational development to ensure competitiveness: increasing the ability of the organization to adapt to changing environmental conditions; updating the management system, organizational structure and culture; setting current goals, introduction of new technologies and methods of work in operational activities and management; creation of new structural units of the organization. Adaptation of domestic business to the rapid pace of market changes requires effctive systematic implementation of a set of actions on strategic management based on business models, innovation management and marketing communications. Emphasis is placed on the main goal of development – to accelerate the process of adaptation to market changes. A balanced model of organizational development based on the education system is proposed, which includes: research of market demand and consumer values; consolidation of the business model in strategic management; audit of human resources; formation of a system of training according to the project of skills; introduction of a structural component of change management based on strategic leadership. The basis of organizational development is: ranking of staf values; introduction of systematic training; formation of a microclimate of mutual assistance in teams; timely informing staf about changes in market factors that will affct the implementation of organizational change; increased material support at the level of strategic management of individual work of operational level managers. The risks of using a balanced learning system within the selected business model are: increasing the ambitions of staf with the development of skills and changing life priorities; the diffilty of directly assessing the effctiveness of learning outcomes; preparation of educational personality-oriented programs. Measures to minimize the risks of implementing a balanced learning system are: teamwork; formation of a structural subdivision of coaches; concluding long-term agreements for certain training programs; motivation systems.
Personnel training as an effective tool of organizational development
Keywords: організаційний розвиток; бізнес-модель; управління змінами; комунікації; organizational development; business model; change management; communications